Ki-67 Evaluation for Clinical Decision in Metastatic Lung Carcinoids: A Proof of Concept - Giuseppe Pelosi; Federica Massa; Gaia Gatti; Luisella Righi; Marco Volante; Nadia Birocco; Patrick Maisonneuve; Angelica Sonzogni; Sergio Harari; Adriana Albini; Mauro Papotti (SAGE Publishing, 2019)
Accrual of metastatic pulmonary carcinoid patients for therapy is usually relied on clinical and histologic characterization, with no role for the proliferation activity as defined by Ki-67 labelling index (LI). A total of 14 carcinoid patients with tumour primaries (TP) and 19 corresponding tumour metastases (TM) were blindly reviewed by 2 different pathologists for necrosis, mitotic count, and Ki-67 LI. Ki-67 LI outperformed histologic subtyping, mitotic count, and necrosis with good to almost excellent (0.40-0.75) inter-observer agreement. About 10% cut-off Ki-67 LI predicted survival better than histology for TP and TM for both observers. The TM patients survived differently according to diverse treatments (somatostatin analogues [SSAs], analogues plus additional treatments except for platinum; platinum-based chemotherapy) in close correlation with <10%, 10% to 20%, and >20% cut-off thresholds of Ki-67 LI, respectively. There was also a trend for an increase in Ki-67 LI in TM as compared with TP. This is the first proof of concept in which a clinical potential is preliminarily suggested for Ki-67 LI to better stratify pulmonary metastatic carcinoid patients for treatment according to a criterion of histology-independent biological aggressiveness.